Socialization of Strategies for Improving the Competitiveness of Local Horticultural Products Through the Application of Ecoenzymes From Organic Waste in Klambir Lima Kebun Village - M. Sidik Tarigan; M. Wasito; Sulardi (Yayasan Sinergi Multidimensi Kreatif, 2025)
This community service activity aims to enhance the competitiveness of local horticultural products. Through socialization and training in the production and application of eco-enzymes from organic waste in Klambir Lima Kebun village, there is a great potential in the horticultural sector, but it still faces challenges in terms of productivity, harvest quality, and the use of environmentally friendly agricultural inputs.Ekoenzim, as a product of organic waste fermentation, has been proven to enhance soil fertility and plant resistance to pests and diseases, while also reducing dependence on chemical fertilizers and pesticides. Through lecture, discussion, and hands-on practice methods, this activity involves local farmers as the main participants. The results of the community service show an increase in public understanding of the benefits of ekoenzim as well as their ability to produce and apply it independently. This activity is expected to encourage sustainable agricultural practices and increase the market value of local horticultural products from Klambir Lima Kebun Village.